Technologies to improve sperm retrieval in men undergoing micro-TESE for NOA - Parviz K Kavoussi; Widi Atmoko; Germar-Michael Pinggera (Asian Journal of Andrology)
Nonobstructive azoospermia (NOA) is considered the most challenging clinical scenario for infertile men and current treatments leave many men unsuccessful at being able to achieve a pregnancy with their partner using their own sperm. Microdissection testicular sperm extraction (micro-TESE) is the choice for men with NOA desiring to father children with their own gametes. Micro-TESE results in the highest numbers of sperm cells retrieved for use with in vitro fertilization/intracytoplasmic sperm injection. With suboptimal micro-TESE success rates of sperm retrieval and then pregnancy and live birth using the retrieved sperm with in vitro fertilization/intracytoplasmic sperm injection, advances to improve outcomes are necessary. This article comprehensively reviews the technologies investigated to date to improve the outcomes for men undergoing micro-TESE.